Immunologic markers, vasculitis-associated autoantibodies, and complement levels in patients with COVID-19 - Maryam Mobini (Wolters Kluwer Medknow Publications, 2021)
Background: The cause of coronavirus disease 2019 (COVID-19) is a virus which can lead to severe acute respiratory syndrome-CoV-2 (SARS-COV-2). There are evidences of involvement of immune system in pathogenesis of this disease. We investigated the presence of various vasculitis-associated autoantibodies and complement levels in patients with COVID-19. Materials and Methods: Patients with severe or critical type of COVID-19 were evaluated for symptoms, signs, and laboratory tests of vasculitis syndromes including rheumatoid factor (RF), antinuclear antibody (ANA), anti-double-stranded DNA, c and p anti-neutrophilic cytoplasmic antibody (c ANCA and P ANCA), and complement levels. Results: The study was performed in forty patients with severe or critical illness. The mean age of the participants was 48.5 ± 9.8 years. All patients had pulmonary involvement in lung computed tomography scans. Vasculitis laboratory test results included RF in two patients, ANA in three patients, and ANCA in one patient. Seventeen (42.5%) patients had hypocomplementemia in one or more complement tests. Four patients expired, of whom three had a decrease in complement level. Conclusion: Decrease in complement levels may predict a critical state of COVID-19 disease. Therefore, measuring its levels may be of great benefit in making earlier decisions to initiate disease-suppressing treatments including corticosteroids.